O26 Gonorrhoea test-of-cure by post maintains return rate. (18th May 2015) - Dennehy, Daniel; Whitlock, Gary; Patel, Sheel; McOwan, Alan; Nwokolo, Nneka
Abstract : Background/introduction: BASHH guidelines recommend test-of-cure (TOC) in all cases of N. gonorrhoeae (NG) 2 weeks after treatment. Previously patients re-attended our clinic in person for TOC. To create capacity in the clinic, we introduced NG TOC postal packs for MSM following treatment. Aim(s)/objectives: To evaluate TOC return rate and patient satisfaction with the service development. Methods: MSM with proven NG were given postal TOC packs at treatment. Each pack contains appropriate NAAT sampling kits for site of diagnosed infection (rectal, throat, urine) and written instructions, patient satisfaction survey and partner notification questionnaire. Patients are instructed to return TOC samples by post in a provided Royal Mail Safebox. We processed samples using our in-house GeneXpert system; results are sent by SMS. Results: During November 2014, 136 NG TOC packs were dispensed. 76 (55.9%) patients returned postal packs; 28 (20.6%) attended for TOC in person, giving overall TOC rate, 76.5%. NG TOC rate in October 2014 was 75.8%. The median time from treatment to sending TOC results was 19 d (IQR:16–24d). NG TOC positivity rate was 12.5% (13/104). 65 patient satisfaction surveys were returned. Most responders found postal TOC easy to use (81.5%; 53/65). 24.6% (16/65) responders would have preferred to attend in person for TOC. Discussion/conclusion: Postal testing is an acceptable NG TOC method which, when combined with the option to return in person, reduced unnecessary follow-up visits while maintaining TOC return rate. The high TOC positivity rate reinforces the importance of continuing to retest patients with NG after treatment.